The mechanism of NAPL layer formation in a microfluidic device with dual-permeability: experiments and numerical simulation. Issue 1 (February 2021) - Wang, Xiaopu; Wang, Xu; He, Tianhao; Li, Yan; Hou, Lianjie
Abstract: In-situ remediation is an important technique for non-aqueous phase liquid (NAPL) contamination remediation in soils. Understanding the formation and distribution of NAPL contaminated layers in heterogeneous soils is essential to propose cost-effective remediation methods. Therefore, a two-dimensional microfluidic device with dual permeability zones was designed to simulate the soil-groundwater system and experimentally investigated the formation process of the NAPL contamination layer. Numerical modeling of phase field coupled with laminar flow was used to simulate the distribution of NAPL in soil-groundwater system, and the formation of NAPL contamination layer under typical groundwater flow rate and wetting angle was evaluated. The NAPL in the low permeable zone formed a stable contamination layer, while the NAPL in the high permeable zone was washed out to varying degrees and mainly resided in the junction of high-low-permeability regions of the chip, with residues of 42.2% and 23.3% in the chip high permeable region at groundwater velocities of 6.17 m/d and 10.16 m/d, respectively, the numerical simulation results were consistent with the experimental observations. This retention was diminished in the high permeable zone as the NAPL-to-wall wetting angle increased. In addition, when the contact angle was increased from 33° (lipophilic) to 108° (hydrophilic), the residual NAPL content in the high permeable zone decreased from 48.86% to 28.22%. This paper provides a reliable visualizable experimental platform for the study of NAPL pollution formation at micro-scale in heterogeneous groundwater system, and lays a foundation for the subsequent optimization of the remediation strategy.